2013
DOI: 10.1039/c3cc45380d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of lipase-catalysed silicone-polyesters and silicone-polyamides at elevated temperatures

Abstract: More and more enzymes are being explored as alternatives to conventional catalysts in chemical reactions. To utilize these biocatalysts to their fullest, it is incumbent on researchers to gain a complete understanding of the reaction conditions that particular enzymes will tolerate. To this end siloxane-containing polyesters and polyamides have been produced via N435-mediated catalysis at temperatures well above the normal denaturation temperature for free CalB. Low molecular weight disiloxane-based acceptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 18 publications
(22 reference statements)
1
30
0
Order By: Relevance
“…Reaction temperatures were set between 130 °C, which is the minimum value required for melting the reactants, and 150 °C, which is the maximum value compatible with enzyme activity. The capacity of CALB to retain polymerization catalytic activity at high temperatures has been reported in several occasions . In this work, an activity test has been carried out to confirm that such capacity is effective under the reaction conditions here used.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…Reaction temperatures were set between 130 °C, which is the minimum value required for melting the reactants, and 150 °C, which is the maximum value compatible with enzyme activity. The capacity of CALB to retain polymerization catalytic activity at high temperatures has been reported in several occasions . In this work, an activity test has been carried out to confirm that such capacity is effective under the reaction conditions here used.…”
Section: Resultsmentioning
confidence: 72%
“…The capacity of CALB to retain polymerization catalytic activity at high temperatures has been reported in several occasions. [26][27][28] In this work, an activity test has been carried out to confirm that such capacity is effective under the reaction conditions here used. Results are given in the SI document (Supporting Information Figure S1), which revealed that CALB retained about 80% of its initial activity after 24 h of reaction of a mixture of CL and c(BF) n at 150 8C.…”
Section: Itmentioning
confidence: 99%
“…Disiloxane diamines and polysiloxane diamines were included in al ater study that was largely focused on examining the thermalt olerance of N435. [92] Our first step was to determine the non-enzymatic rate of polyesterification and polyamidation, so that we could correct the observed rates to better reflect the enzymatic process. The non-enzymatic rate of ester formation was zero and resulted in the recovery of starting materials.…”
Section: Polymerizationmentioning
confidence: 99%
“…Zelisko and Framptona ttributedt he higher thermals tability of the enzyme to favorable interactions between the enzymea nd hy-drophobic siloxanes. [92] It is known that enzymes can maintain structuralr igidity in organic solvents if the solvents ares ufficiently nonpolar,s oa st ol imit the degree of thermally induced motion. [101,102] Because Frampton and Zelisko elected to perform reactions in the absence of solvent, the monomers themselves assumed that particularrole.…”
Section: Thermal Tolerance Of Calb In the Presence Of Siloxanesmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Among them, Candida antarctica lipase B (CALB) immobilized on acrylic resin (commercially available as Novozym 435) is the most favorable biocatalyst since it works well with diverse monomer substrates at mild temperatures and even at elevated temperatures. [21][22][23] So far most research in this fi eld still focused on enzymatic polymerization of conventional petroleumbased monomers. [ 24,25 ] The use of biobased monomers in biocatalytic approaches towards polyester materials is an appealing topic both in academic and industrial fi elds.…”
Section: Introductionmentioning
confidence: 99%